FRASA ENDOSENTRIS PADA BAHASA JEPANG - Lina Rosliana (IZUMI, 2015)
Phrase is a combination word, which is consisting of two words or more and become part of a sentence. Phrase can not be said as a clause because the phrase does not exceed the limit function. Structure of phrase in Japanese has similarities with the clauses and compound words in Indonesian, so it is interesting to analyze and see the difference. This study discusses the definition of the phrase in Japanese, the difference with the clauses and compound words seen from the form, the structure of the phrase, and the category of phrase.